Kultur Antera untuk Mendapatkan Galur Padi Toleran Salinitas - Safitri, Heni; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Ardie, dan Sintho Wahyuning (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTHaploid breeding through anther culture allows shortening of the breeding cycle and production of homozygous lines from a segregating population in the immediate generation. This technique has been used for crop improvement especially in rice. The objective of this research was to determine regeneration ability of twelve F1s, derived from reciprocal crossing between high yielding rice variety and rice tolerance to salinity, through anther culture. Completely randomized design with 20 replications was used in this research. Medium for callus induction was based on N6 medium + 2.0 mg NAA L-1 + 0.5 mg kinetin L-1 + 1 mM putrescine, while regeneration medium was based on MS + 0.5 mg NAA L-1 + 2.0 mg kinetin L-1 + 1 mM putrescine. Rooting were done in MS medium + 0.5 mg IBA L-1 + 1 mM putrescine. The result indicated that F1 derived from IR77674/Inpari 29 (3.1% green plants/total anther) was the most responsive genotypes in rice anther culture (high anther culture ability). After greenhouse grow out 125 putative double haploid plants were obtained (41.5% from total acclimated green plantlets).  Keywords: double haploid, green planlets, indica rice, salt tolerance